Dilemmas and ethical decision-making in Knowledge Organization - Suellen Oliveira Milani (Informatio)
Librarians assign classification numbers and indexing terms to documents through knowledge representation and knowledge organization systems, such as classification schemes, indexing languages, etc. When representation is not carried out in a reliable way, censorship, omission, or misrepresentation of information may occur. Librarians will have to deal with ethical values as well as cultural and linguistic boundaries, and they will face dilemmas that require ethical decision-making. Once librarians realize that unresolved ethical problems can be harmful to their community users, they should be respectful. Based on reports from specialized international literature, this paper proposes a discussion about the ways in which knowledge organization tools may present ethical dilemmas for librarians. By approaching the issue from an exploratory, bibliographic, and qualitative perspective, this study aims to provide elements for discussion both in courses related to knowledge organization and other areas concerned with ethical issues though an interdisciplinary approach.